LIDOCAINE IN VENTRICULAR TACHYCARDIA WITH HEMODYNAMICALLY UNSTABLE WHO REFUSE CARDIOVERSION, IS IT THE FIRST CHOICE OR NOT? - Yuri Savitri; Ayu Permata Sari; Dio Gusfanny; Gisca Chairiyah Ami; Isra Namira (Fakultas Kedokteran Universitas Malikussaleh, 2022)
Sudden cardiac death (SCD) is a vital public health issue, accountable for almost 50% of all cardiovascular deaths. In the last three decades, SCD was the leading cause for almost 230000 to 350000 deaths per annum in the United States. Ventricular arrhythmias account for 25% to 36% of witnessed sudden cardiac arrests (SCA) at home and 38% to 79% of witnessed SCA in public. The goals of ventricular arrhythmia management include symptom relief, improving quality of life, reducing implantable cardioverter defibrillator shocks, preventing deterioration of left ventricular function, reducing risk of arrhythmic death, and potentially improving overall survival. Based on the ACLS guideline, each tachyarrythmia with a pulse should be given synchronized cardioversion, however, when such action could not be performed for various reasons, and showed wide QRS 0,12, intravenous or antiarrthytmia might serve as a possible treatment. If intravena antiarrhytmics are given, amiodarone may be considered. Amiodarone is also effective in preventing recurrence of monomorphic VT. Lidocaine is less effective in terminating VT than procainamide, sotalol and amiodarone. Lidocaine may be considered second-line antiarrthythmic therapy for monomorphic VT.